The complete chloroplast and mitochondrial genomes of Hyunsasi tree, Populus alba x Populus glandulosa (Salicaceae). Issue 2 (3rd July 2019) - Park, Jongsun; Kim, Yongsung; Xi, Hong; Kwon, Woochan; Kwon, Mi
Abstract: Populus alba x Populus glandulosa is a hybrid species made by Dr. Hyun. It is called as Hyunsasi tree in Korea. It has been used as a good resource for genetic engineering because it is sterile. Here, we presented its complete chloroplast and mitochondrial genomes: chloroplast genome is identical to that of P. alba (156, 505 bp and 129 genes covering 84 protein-coding genes, 37 tRNAs, and eight rRNAs) and mitochondrial genome is 813, 261 bp long and GC ratio is 44.9%. It contains 59 genes containing 32 protein-coding genes, 22 tRNAs, and three rRNAs. Based on alignment with P. tremula x P. alba mitochondrial genome, 1, 752 single nucleotide polymorphisms (SNPs; 0.22%) and 41, 506 insertion and deletions (INDELs; 5.10%) are found. Phylogenetic trees based on chloroplast and mitochondrial genomes show different topology in four Populus species, indicating that both genomes may be evolved in different ways after common ancestors of Populus genus.